Project governance frameworks of large public projects in Iceland and Norway : perceptions and practices - Steinunn Marta Gunnlaugsdóttir 1982- (2019)
This study is a contribution to the debate about the over-running of large public projects in terms of cost and time. The main aim of the study is to examine the current state of project governance when it comes to large investment projects in Iceland and Norway. In Iceland, ministries and agencies are required to follow the law on public projects followed with official procedure guidelines when it comes to carrying out initial project analysis. The Norwegian government has successfully developed a project governance framework that is intended to thoroughly analyse projects in their early stages. That analysis seeks out solutions for projects at a conceptual level. Also, the Norwegian model requires the use of external parties to quality assure that work. This thesis seeks to define the elements and methods that characterize a robust project governance framework. The main objective is to benchmark these criteria with the content of the Icelandic law on public project arrangement. Also, examine practices carried out in the ministries and agencies through interviews with stakeholders. The result indicates that the official guidelines include only a basic set of criteria. Most agencies and ministries exceed the given requirements, but not significantly. A more detailed analysis of critical factors at an early stage is needed and more consistency in practices within the administrative system of project governance, as well as more emphasis should be set on ethical values, such as transparency and accountability. To increase consistency and transparency at an early stage of decision-making, the legislator must provide a more significant requirement that standardized methods be applied. Rannsókn þessi er innlegg í umræðuna um yfirkeyrslu stórra opinberra verkefna er varðar kostnað og tíma. Megin markmið rannsóknarinnar er að kanna núverandi stöðu verkefnastjórnsýslu hins opinbera þegar kemur að viðamiklum fjárfestingarverkefnum á Íslandi og í Noregi. Á Íslandi er ráðuneytum og opinberum stofnunum gert að framfylgja ...